Development of bamboo- (Bambusa bambos) based bio-fence to protect field crops: Insights from a study in India's Bundelkhand region - Kumar, Dinesh; Yadav, Ram Swaroop; Kadam, Darshan Manikrao; Ahirwar, Lakhan Lal; Dohare, Anil Kumar; Singh, Gautam (Frontiers in Ecology and Evolution, 2022)
Stray/wild animals can cause serious damages to crops, leading to accusations and counter accusations among villagers. In the Bundelkhand region of India, this problem is more severe due to “Anna Pratha,” that is, letting loose animals to open graze. Protective measures employed by farmers (barbed wire fencing, conventional fencing, etc.) are not fully effective and also require periodical maintenance, which involves additional costs and manpower. This necessitates the evolution of a cost-effective and long-term solution to minimize the problem. The current study seeks to evaluate the potential of thorny bamboo (Bambusa bambos) as a bio-fence creating deterrence to stray/wild animals at the ICAR—IISWC RC, the research farm of Datia, Madhya Pradesh, India. After 21 months of planting, bamboo plants attained the maximum plant height up to 4.47 m with the highest clump spread diameter of 30.50 cm. However, the growth of the bamboo bio-fence to be effective depends on the edaphic and management conditions. The findings revealed that planting bamboo at a distance of 80.00 cm in the continuous trench can be an effective bio-fence to avoid man–animal conflict. Huge crop losses were reported before the establishment of a bio-fence. In 2021–2022 (when bamboo plants turned into a closely spaced thicket, making a bio-fence), only two incidents of the invasion of animals were reported with no crop damage. The initial cost to develop a bamboo bio-fence was estimated at INR 5,796 for a length of 100 m. Therefore, the present study suggests that bamboo bio-fencing is an economical and effective crop protection measure against damage by wild/stray animals.